FIGURE 4 in A new species of Sphaerodoridium Lützen, 1961 from Iceland (Polychaeta: Sphaerodoridae) - Moreira, Juan; Parapar, Julio (Zenodo, 2015)
FIGURE 4. Sphaerodoridium guerritai sp. nov. A, female, chaetiger 9, ventrolateral view, right side; B, generalized schematic arrangement of ventral papillae in female, chaetigers 9–11. A: Paratype IINH 33099; B: Allotype IINH 33096. Legend of symbols for B: U-shaped symbols = parapodia; small circles among parapodia = lateral body papillae; large circles and other small circles = ventral body papillae; rectangles = nephridial papillae; oval at chaetiger 9 = tubercle-like ventral reproductive structure. Published as part of Moreira, Juan & Parapar, Julio, 2015, A new species of Sphaerodoridium Lützen, 1961 from Iceland (Polychaeta: Sphaerodoridae), pp. 91-105 in Zootaxa 3911 (1) on page 97, DOI:10.11646/zootaxa.3911.1.5, http://zenodo.org/record/236683